2016
DOI: 10.1501/tarimbil_0000001393
|View full text |Cite
|
Sign up to set email alerts
|

The factors affecting heavy metal levels in the muscle tissues of whiting (merlangius merlangus) and red mullet (mullus barbatus)

Abstract: This study aims to determine heavy metal accumulation levels in the muscles tissues of two economically most important demersal fish species in the Eastern Black Sea, Turkey, red mullet (Mullus barbatus) and whiting (Merlangius merlangus), and evaluate the effects of fish species, sampling locations, fishing season and size groups on heavy metal accumulation levels. Chromium (Cr), manganese (Mn), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), arsenic (As), cadmium (Cd) and lead (Pb) concentrations in fish m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, the characteristics of pH, temperature and alkalinity did not affect the accumulation of Cu in the fish (Okpashi et al, 2018). Another research found that the order of heavy metals concentration in the fish muscle was Zn > As > Cu > Mn > Cr > Ni > Cd > Co >Pb (Alkan et al, 2016). Meanwhile, another research found that the concentration of metals in the fish muscle was in the following order: Fe > Zn > Cu > Mn > Pb > Cd (Miller, et al, 2013).…”
Section: The Potential Sources Of Cu In Rawapening Lakementioning
confidence: 99%
“…However, the characteristics of pH, temperature and alkalinity did not affect the accumulation of Cu in the fish (Okpashi et al, 2018). Another research found that the order of heavy metals concentration in the fish muscle was Zn > As > Cu > Mn > Cr > Ni > Cd > Co >Pb (Alkan et al, 2016). Meanwhile, another research found that the concentration of metals in the fish muscle was in the following order: Fe > Zn > Cu > Mn > Pb > Cd (Miller, et al, 2013).…”
Section: The Potential Sources Of Cu In Rawapening Lakementioning
confidence: 99%
“…The precise line between whether a metal should be considered beneficial or harmful is dependent on dose limits and exposure frequencies (Alkan et al 2016;Leonard et al 2022;Yildiz et al 2023 ). Trace elements such as copper, manganese, zinc, iron are essential for the metabolic activities in humans and other living organisms, which however can be toxic and cause severe damage at high levels of bioaccumulation in tissues (Çağlak & Karsli 2014;Makedonski et al 2017).…”
Section: Introductionmentioning
confidence: 99%